INFLUENCER MARKETING - CHOOSE THE RIGHT OPINION LEADER TO PROMOTE YOUR BRAND (Web of Teachers: Inderscience Research, 2025)
Our article is dedicated to the importance of choosing the right opinion leader (influencer) for successful brand promotion in the digital economy. In recent years, influencer marketing has become an important part of the strategies of companies seeking to effectively interact with their target audience and increase trust in their brand. However, successful cooperation with influencers requires a careful approach to choosing a partner, which includes an analysis of the audience, the image of the opinion leader, as well as the compliance of their values and content with the brand.